Sm-doped Pb(Mg1/3Nb2/3)O3-xPbTiO3 piezocatalyst: Exploring the relationship between piezoelectric property and piezocatalytic activity. (December 2019) - Yuan, Baowei; Wu, Jiang; Qin, Ni; Lin, Enzhu; Kang, Zihan; Bao, Dinghua
Graphical abstract: Highlights: The piezocatalytic activity exhibits a linear relationship with the piezoelectric coefficient of Sm-PMN-xPT, which indicate the essential role of piezoelectric coefficient in the piezocatalytic performance. The Sm-PMN-0.29PT sample with the optimum piezoelectric coefficient exhibits an ultra-high rate constant of piezocatalytic reaction, which is superior than most of the reported materials with piezocatalytic activity. Free radicals and dye degradation intermediates were detected in the piezocatalytic process, demonstrating the catalytic nature of piezoelectricity induced dye degradation. Abstract: The piezocatalytic performance of Sm-doped Pb(Mg1/3 Nb2/3 )O3 - x PbTiO3 solid solutions, which exhibit ultrahigh piezoelectric coefficient with a dependence on PbTiO3 content, was thoroughly investigated. We focused mainly on the influence of piezoelectric property modulation on the piezocatalytic performance of the materials by composition arrangement. The maximal piezocatalytic activity was achieved as the composition approached the morphotropic phase boundary (MPB) at x = 0.29, in which the piezoelectric coefficient also reached the maximum. The linear relationship between the two properties proves that the piezoelectric effect plays a key role in the piezocatalytic performance. As a direct evidence of catalytic reactions, free radicals were detected by electron spin resonance (ESR) technique. Revolution of intermediate products observed by liquid chromatography-mass spectrometry (LC–MS) further confirms the catalytic reactions in the piezoelectricity induced dye degradation process. This work is of great significance for understanding the mechanism of piezocatalytic effect.